The Inter-Branch Rivalry in the American Government : Presidential excutive Decrees versus Congressional Legistions - Menni, Mokhtar, Fatma Besma (University of El-oued, 2022)
The American government is ruled by three main branches legislative, executive, and judicial .This study focuses on the executive and the legislative ones .According to the American constitution , governmental power is vested in the two previous branches .This dissertation aims at investigating the inter-branch rivalry among these branches and how it occurs through conducting a historical-descriptive analysis. In the light of this analysis ,three hypotheses have been raised: the first introducing the Powers of the Presidential Executive branch . The second tackles the process of enacting laws and the authorities given to the president. The last hypothesis mentions how inter-branch rivalry occurs between the two distinctive branches .After gathering the data of this work from the group of sources ,we found that both the Legislative and Executive branches face a kind of rivalry among their authorities .Nevertheless, it is still the role of both of them in serving the American government ,So as a result, we can say that the kind of relationship between the two is a complementary one.
Keywords: American government ,Executive ,Legislation ,Rivalry